La evolución paleogeográfica de los Llanos Leridanos (Sector oriental de la Depresión del Ebro) durante el Cuaternario - Peña Monné, José Luis (Geographicalia, 2017)
A major erosive depression characterized by its general planitude (Pla de Lleida, Plá d'Urgell) has been individualized in the eastern sector of the Ebro Basin. There, as a consequence of pronounced alternating dynamic phases, a system of nine quaternary terrace fligths may be recognized, as well as important changes in the palaeogeographic pattern of the Plád'Urgell and Noguera-Ribagorzana areas